1994
DOI: 10.2527/1994.7292385x
|View full text |Cite
|
Sign up to set email alerts
|

The role of feed consumption and feed efficiency in copper-stimulated growth

Abstract: Two experiments were conducted to study the role of feed intake and feed efficiency in Cu-stimulated growth of weanling pigs. In Exp. 1, 42 pigs were randomly assigned into three treatments: 1) control: ad libitum access to a corn-soybean meal-dried whey basal diet; 2) ad libitum/Cu: ad libitum access to the basal diet supplemented with 215 ppm of Cu; or 3) pair-fed/Cu: pair-fed the Cu-supplemented diet to the level of the control. Over the 14-d experiment, the ad libitum/Cu pigs had greater (P < .05) ADG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 9 publications
(16 reference statements)
6
33
1
7
Order By: Relevance
“…However, studies by Aulerich and Ringer (1976) indicated superior weight gains in male mink fed supplemental Cu at the 50 mg/kg level. Besides being an essential nutrient, Cu has received considerable attention due to its growth promoting and antimicrobial properties in animals when it has been fed at prophylactic levels (Zhou et al 1994b;Pang et al 2009;Lu et al 2010;Karimi et al 2011). Studies by Dove and Haydon (1992) and Dove (1995) have indicated that addition of 250 ppm Cu improved digestibility and utilization of the fat of weaned pigs.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies by Aulerich and Ringer (1976) indicated superior weight gains in male mink fed supplemental Cu at the 50 mg/kg level. Besides being an essential nutrient, Cu has received considerable attention due to its growth promoting and antimicrobial properties in animals when it has been fed at prophylactic levels (Zhou et al 1994b;Pang et al 2009;Lu et al 2010;Karimi et al 2011). Studies by Dove and Haydon (1992) and Dove (1995) have indicated that addition of 250 ppm Cu improved digestibility and utilization of the fat of weaned pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Creech et al (2004) previously reported that trace mineral sources exerted no effects on performance during the growing or gilt development phase. Coffey et al (1994) and Zhou et al (1994) previously reported that additions of Cu from copper-lysine complexes resulted in improved pig performance as compared with copper sulphate. Other researchers, however, have noted no differences in growth-promoting activity between the two Cu sources (van Heugten and Coffey, 1992).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, some studies with organic forms of Cu and Zn have also been shown to reduce mineral excretion (Creech et al, 2004) and improve performance when included at similar levels to inorganic sources (Zhou et al, 1994;Veum et al, 1995), or can be incorporated at lower dietary levels than those in the inorganic forms without negatively affecting growth performance (Mullan et al, 2002). Results from Smits and Henman (2000) indicated that Cu could be reduced from 150 mg/kg Cu sulfate to 40 mg/kg in the form of Cu proteinate amino acid chelate in grower diets, while Fremaut (2003) showed that Zn, Fe, Mn and Cu could be reduced to 36, 39, 18 and 7 mg/kg (30% of normal levels used in Belgium) if all were included in the proteinate amino acid chelate form.…”
Section: Introductionmentioning
confidence: 99%